Biological status and dietary intakes of Iron, Zinc and Vitamin A among women and preschool children in rural Burkina Faso - Martin-Prével, Yves; Allemand, Pauline; Nikiema, Laetitia; Ayassou, Kossiwavi A.; Ouedraogo, Henri Gautier; Moursi, Mourad; De Moura, Fabiana F. (Public Library of Science, 2016)
Background